Studi Komparatif: Pengaruh Harga Saham Bank Mandiri dan Bank Syariah Indonesia terhadap Indeks Harga Saham Gabungan (IHSG) Periode 2019-2024 - Shodiq, Ahmad Naufal Jafar; Nugraha, Budi Sutiono Pratama (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the effect of the share prices of Bank Mandiri (BMRI) and Bank Syariah Indonesia (BRIS) on the Composite Stock Price Index (JCI) for the 2019-2024 period. This study uses a quantitative method with secondary data in the form of monthly stock price data totaling 72 observations (N=72) for each variable, obtained from financial statements and stock price data. Data were analyzed using multiple linear regression to test for simultaneous and partial influences, the F test to test for simultaneous influences, the t-test to test for partial influences, the Durbin-Watson test to test for autocorrelation, the Glejser test to test heteroscedasticity, and the Independent Samples t-test to test the difference in influence between BMRI and BRIS. The results of the study show that BMRI's share price has a significant positive effect on JCI, while BRIS's share price has a significant negative effect. Simultaneously, BMRI and BRIS had a significant effect on the JCI with a contribution of 72.6%. The Independent Samples t-test showed a significant difference in influence between BMRI and BRIS on the JCI. This study found that there were indications of positive autocorrelation, but there were no problems of multicollinearity and heteroscedasticity. The implication of this study is that market stability-oriented investors are advised to make BMRI stock the main portfolio, while investors with a high risk profile can consider BRIS as a diversification alternative with an appropriate risk management strategy. The study also provides recommendations for regulators, academics, and advanced researchers.